Cowpea seeds from plants subjected to restricted-and full-irrigation regimes show differential phytochemical activity - MirReza Miri; Farshad Ghooshchi; Hamid Reza Tohidi Moghadam; HamidReza Larijani; Pourang Kasraie (Botanical Studies, 2022)
Abstract Background Water scarcity is responsible for losses in the yield of many plants and this is expected to continue due to climate change. However, cowpea which is known for its drought tolerance, is considered as a plant without limitations to climate change. A two-year experiment was conducted to evaluate the effect of water restriction on phenolic compounds, antioxidant capacity and leaf nutrients concentration of four cultivars of cowpea at different growth stages. At second leaf stage, two irrigation regimes were initiated (Water irrigation was applied after 75% and 55% of field capacity, as well watered and drought stress treatment, respectively).Plants samples were collectedat three stages(immature pod, immature seed and dry seed stage) for total phenol and flavonoids content, ortho-diphenols andantioxidant capacity measurement and leaves sampling for nutrients concentration. Results The results indicated that polyphenolic compounds and antioxidant capacity increased under drought conditions. However, in both irrigation regimes, immature pods had the higher polyphenolic compounds, antioxidant capacity and leaf nutrients concentration rather than immature seeds and dry seeds. Among the genotypes, ILC482 revealed the highest content of total phenolics and ortho-diphenols (6.9 and 3.57 mg GA g−1dry weight, respectively). In addition, nitrogen, phosphorus and magnesium concentration of leaves were higher in ILC482 genotype. Under drought stress, ILC482 maintained higher ABTS radical scavenging capacity (0.0083 mmol Trolox g−1dry weight) compared to other genotypes. Conclusions It is suggested that drought stress affect the quality of cowpea productions through polyphenolic compounds, ABTS and DPPH radical scavenging capacity which can be used as a helpful strategy to save water in the regions where water is scare.